Green synthesis of NiO nanoparticles using Nigella sativa extract and their enhanced electro-catalytic activity for the 4-nitrophenol degradation. (June 2021) - Boudiaf, Moussa; Messai, Youcef; Bentouhami, Embarek; Schmutz, Marck; Blanck, Christian; Ruhlmann, Laurent; Bezzi, Hamza; Tairi, Latifa; Eddine Mekki, Djamel
Abstract: Green-synthesized NiO nanoparticles (NiONPS ) have been developed using Nigella Sativa seeds extract as stabilizing agent. The pH of the solution has been modulated, by the addition of NaBH4 . NiONPs have been characterized by XRD, FTIR, SEM and TEM. FTIR measurements and TEM images highlighted that NiONPs were surrounded by some biological compounds coming from the extract. The total reduction of 4-nitrophenol to 4-aminophenol corresponding to the catalytic activity of NiONPs was occurred at pH7, pH9 and pH11 in 60min, 10min and 45min respectively. These results revealed that the best catalytic activity is obtained at pH9 which is confirmed by electrocatalytical activity measurements where the resistance charge transfer corresponding is 53.7 Ω cm 2 and the Warburg constant 0.0395Ωs -1/2 related a good ion diffusion, indicated consequently an increase number of electroactive sites. Thus, the carrier charges generated in the NiO mass can easily reach the surface which contribute to the reduction of 4-nitrophenol. Graphical abstract: Image 1 Highlights: The catalyst was synthesized via green method as function of pH values. The NiO nanoparticles exhibit better catalytic and electrocatalytic activities toward 4-Nitrophenol reduction. pH values has an influence on the number of active sites. The catalyst that has low charge transfer resistance and good ions diffusion has better catalytic activity.